Recycling of Waste Cloths for Greener Future - Ravikant Nanwatkar; Tejas Rasal; Rohan Manthale; Dev Kalbende; Darshan Meshram (International Journal of Environmental Noise and Pollution Control, 2026)
The exponential development of fashion and textile industries around the world largely increase, the production of waste cloth has grown by a steep rate, presenting serious environmental issues in terms of landfill garbage, greenhouse gas emissions and waste depletion. Millions of tons of textiles are disposed of every year, and the recycling of waste cloth has become one of the critical solutions to a circular economy in the process of eliminating environmental degradation. This paper examines the recycling of waste fabrics as an efficient way of reducing waste textiles besides promoting sustainable development. The main aim of the given research is to compare the possibility of recycling of different types of textiles using mechanical, chemical depolymerization, and imaginative upcycling techniques, in terms of their feasibility, efficiency, and environmental advantages. The research is a mixed approach where literature review, experimental analysis, and case study of textile recycling industries have been used. The data is processed to determine material recovery, energy use, and carbon footprint impacts of each approach. The most critical results show that mechanical recycling can be used to recycle natural fibers, including cotton and wool, but chemical recycling can be used to recycle synthetic fibers, including polyester, and recover almost virgin quality fibers. Despite being small-scale, upcycling practices have a great impact on the local economies and social sustainability through job creation and promotion of eco- friendly consumer behavior. In general, the study shows that the effective waste cloth recycling can significantly decrease the landfills, save the natural resources, and decrease the emission of CO 2. Textile recycling can be a transformative element in attaining a green, more sustainable future through the addition of recycling technologies, public awareness and policy support. This paper explains why the implementation of the circular textile systems should become the foundation of worldwide environmental sustainability and conscious consumption.
Keywords: Cloth Waste Reduction; Sustainable Fashion; Upcycling; green technology; resource conservation